Influence of the ICTs in the appropriation of concepts about analogue electronics by the seventh grade students of basic education - Hernández, Arnulfo Parada; Suarez Aguilar, Zagalo Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2014)
To do so, it was necessary to select a control group and an experimental group where it could be possible to design, implement and evaluate a teaching unit on basic electronics. On one hand, a traditional class methodology was used with the first group, on the other hand, the second group followed the model proposed by Fundación Colombiana Gabriel Piedrahita Uribe. In order to determine the impact of this study, a quasi-experimental research has been chosen. Its results showed that the use of ICTs in fact improved the internalization of concepts of basic analogic electronics in the target population, increasing 1.4 times the possibility of learning the topic compared to the control group. This association varies in the evaluation of the subtopics, showing that in some participants the acquisition of concepts improved thanks to the use ICTs, and in others, it is shown that their use had no impact on them.